2014
DOI: 10.1136/medethics-2013-101810
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex parenting: IVG and the generations to come

Abstract: Recent breakthroughs in stem cell differentiation and reprogramming suggest that functional human gametes could soon be created in vitro. While the ethical debate on the uses of in vitro generated gametes (IVG) was originally constrained by the fact that they could be derived only from embryonic stem cell lines, the advent of somatic cell reprogramming, with the possibility to easily derive human induced pluripotent stem cells from any individual, affords now a major leap in the feasibility of IVG derivation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…There are "minimal" forms of biological motherhood, either genetic (as in mitochondrial donation/replacement where the genetic-biological "motherhood" is minimal), or non-genetic (e.g., gestational surrogacy). In addition, under the (still experimental) prospect of "in vitro generated gametes" (IVG) [113], biologic motherhood may quantitatively be varying with regard to each single case.…”
Section: The Borderline Is Shifting Toward Normality Broadening What mentioning
confidence: 99%
See 3 more Smart Citations
“…There are "minimal" forms of biological motherhood, either genetic (as in mitochondrial donation/replacement where the genetic-biological "motherhood" is minimal), or non-genetic (e.g., gestational surrogacy). In addition, under the (still experimental) prospect of "in vitro generated gametes" (IVG) [113], biologic motherhood may quantitatively be varying with regard to each single case.…”
Section: The Borderline Is Shifting Toward Normality Broadening What mentioning
confidence: 99%
“…Such gametes may enhance the reproductive ability of samesex couples or post-menopausal women [113], two categories for which being a parent is considered unnatural. Besides, in case of oocytes shared donation between the partners of a lesbian couple ("shared biologic motherhood") [114] there is a combination of biologic and gestational motherhood [115].…”
Section: The Borderline Is Shifting Toward Normality Broadening What mentioning
confidence: 99%
See 2 more Smart Citations
“…Those in the legal and bioethics literature have suggested that IVG may in the future confront us with a still more complex conceptual future, where the number of genetic parents is no longer limited to two. The scientific literature has not yet proven feasibility but, for the purpose of thinking through the implications, consider the speculative possibility of so-called multiplex parenting, where one gamete is derived from two individuals and combined with the gamete of a third individual (24). Would we view each of those three as equal genetic parents, or do we give greater rights and duties to the parent who contributed more genetic material?…”
Section: Regulation and Ethicsmentioning
confidence: 99%